Networking as a strategy for gender equality in professional life - Innreiter-Moser, Cäcilia; Schnugg, Claudia (Momentum Quarterly, 2012)
Networking is a crucial factor for success at work. As men and women have unequal access to professional networks and handle network contacts differently, the use of networks leads to inequality in men’s and women’s success at work. In this study we use qualitative interviews to understand where these differences come from and why those differences are still observable although many professional networks are nowadays open to women and many women networks have been founded during the last two decades. We can show a slow change in the women’s perception of networks and how they handle distinct kinds of contacts (strong and weak ties). Further, we analyze this phenomenon from a neo-institutional perspective to understand why it takes so long to establish networking as a tool of women for success at work and why new women networks are not as effective as traditional networks. Concluding, we use this neo-institutional perspective to make suggestions of how to overcome the current situation, ease networking for women and make networking for women more successful.